WETTING ON LINES AND LATTICES OF CYLINDERS - Osborn, W; Yeomans, J (1995)
This paper discusses wetting and capillary condensation transitions on a line and a rectangular array of cylinders using an interface potential formalism. For a line of cylinders, there is a capillary condensation transition followed by complete wetting if the cylinders are sufficiently close together. Both transitions disappear as the cylinder separation is increased. The dependence of the wetting phase diagram of a rectangular array of cylinders is discussed as a function of the chemical potential, substrate-fluid interaction strength, and surface tension. © 1995 The American Physical Society.